Identity based identification from algebraic coding theory - YANG, Guomin (Institutional Knowledge at Singapore Management University, 2014)
Cryptographic identification schemes allow a remote user to prove his/her identity to a verifier who holds some public information of the user, such as the user public key or identity. Most of the existing cryptographic identification schemes are based on numbertheoretic hard problems such as Discrete Log and Factorization. This paper focuses on the design and analysis of identity based identification (IBI) schemes based on algebraic coding theory. We first revisit an existing code-based IBI scheme which is derived by combining the Courtois–Finiasz–Sendrier signature scheme and the Stern zero-knowledge identification scheme. Previous results have shown that this IBI scheme is secure under passive attacks. In this paper, we prove that the scheme in fact can resist active attacks. However, whether the scheme can be proven secure under concurrent attacks (the most powerful attacks against identification schemes) remains open. In addition, we show that it is difficult to apply the conventional OR-proof approach to this particular IBI scheme in order to obtain concurrent security. We then construct a special OR-proof variant of this scheme and prove that the resulting IBI scheme is secure under concurrent attacks.